2020
DOI: 10.1038/s41598-020-68334-2
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive tuning of infrared emission using VO2 thin films

Abstract: Phase-transition materials provide exciting opportunities for controlling optical properties of photonic devices dynamically. Here, we systematically investigate the infrared emission from a thin film of vanadium dioxide (VO 2). We experimentally demonstrate that such thin films are promising candidates to tune and control the thermal radiation of an underlying hot body with different emissivity features. In particular, we studied two different heat sources with completely different emissivity features, i.e. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The transition temperature setting of vanadium dioxide is usually controlled via impurity doping with lower- and higher-valence transition metals, such as W, Nb, Cr, Mo, and Ti. However, to obtain highly effective thermochromic and electrochromic properties, a thin film of pure-phase VO 2 is required. For this purpose, various synthesis methods, such as strain-induced single-crystal substrates with the most preferred orientation, buffer layers, narrow oxygen partial pressures, and optimal growth temperatures, have already been studied. More recently, VO 2 has been adopted as a next-generation material with dynamic color adjustment for reflectors or transmitters because of its significantly low phase change, low power consumption, low toxicity, low-effort manufacture, wide range of fabrication techniques, stability, and reversible electrically and optically activated tuning. In particular, changes in optical properties, if induced in the visible spectral range, offer considerable benefits and ease of detection. Recently, photonic materials that are color-tunable in the visible spectral range, making them extremely attractive for application in temperature indicators, displays, memory, and other switchable optoelectronic devices, have been developed. For example, Song et al reported, based on their modeling results, that vanadium dioxide-based metamaterial absorbers for active color rendering and multiband photodetection can be realized .…”
Section: Introductionmentioning
confidence: 99%
“…The transition temperature setting of vanadium dioxide is usually controlled via impurity doping with lower- and higher-valence transition metals, such as W, Nb, Cr, Mo, and Ti. However, to obtain highly effective thermochromic and electrochromic properties, a thin film of pure-phase VO 2 is required. For this purpose, various synthesis methods, such as strain-induced single-crystal substrates with the most preferred orientation, buffer layers, narrow oxygen partial pressures, and optimal growth temperatures, have already been studied. More recently, VO 2 has been adopted as a next-generation material with dynamic color adjustment for reflectors or transmitters because of its significantly low phase change, low power consumption, low toxicity, low-effort manufacture, wide range of fabrication techniques, stability, and reversible electrically and optically activated tuning. In particular, changes in optical properties, if induced in the visible spectral range, offer considerable benefits and ease of detection. Recently, photonic materials that are color-tunable in the visible spectral range, making them extremely attractive for application in temperature indicators, displays, memory, and other switchable optoelectronic devices, have been developed. For example, Song et al reported, based on their modeling results, that vanadium dioxide-based metamaterial absorbers for active color rendering and multiband photodetection can be realized .…”
Section: Introductionmentioning
confidence: 99%
“…When the temperature applied to VO 2 increases beyond a critical point (T c ), insulator-to-metal transition (IMT) takes place, which renders its monoclinic (insulator) phase rutile (metallic). 10 While the microscopic dynamics of this intriguing phase transition for VO 2 remains elusive, 11 the experimental implementation of it in devices has been successful in the recent decade. The lower T c required for the IMT of VO 2 than that of other phase-change materials, 9,12 along with a variety of possible routes to achieve IMT (thermally, 13 electrically, 14 mechanically, 15 and optically 16,17 ), has provided ample opportunities to tailor the IMT of VO 2 to numerous applications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…18,19 The essence of optical modulation in the mentioned photonic applications is the IMT of VO 2 , which marks a sizeable change in the refractive index of this material. Some of the notable applications include optical diodes, 20 tunable metamaterials, 21−23 thermal emitters, 10,24 and infrared absorbers. 25 Marrying the tunability of VO 2 and the rich optical response of vdW materials through intricate designs, researchers have successfully demonstrated devices with tunable optical responses.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations